2012
DOI: 10.1186/1471-2407-12-29
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell proliferation and survival genes by estradiol-repressed microRNAs in breast cancer cells

Abstract: BackgroundIn estrogen responsive MCF-7 cells, estradiol (E2) binding to ERα leads to transcriptional regulation of genes involved in the control of cell proliferation and survival. MicroRNAs (miRNAs) have emerged as key post-transcriptional regulators of gene expression. The aim of this study was to explore whether miRNAs were involved in hormonally regulated expression of estrogen responsive genes.MethodsWestern blot and QPCR were used to determine the expression of estrogen responsive genes and miRNAs respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 55 publications
(70 reference statements)
9
52
3
1
Order By: Relevance
“…In the present study, it was found that treatment with E2 induced a significant decrease in miR-203 levels in breast cancer cells, suggesting that it may be involved in E2-mediated malignant progression of breast cancer MCF-7 cells. Yu et al also reported that E2 significantly induced bcl-2, cyclin D1 and survivin expression by suppressing the levels of miR-16, miR-143 and miR-203 in MCF-7 cells (35), consistent with the current findings.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, it was found that treatment with E2 induced a significant decrease in miR-203 levels in breast cancer cells, suggesting that it may be involved in E2-mediated malignant progression of breast cancer MCF-7 cells. Yu et al also reported that E2 significantly induced bcl-2, cyclin D1 and survivin expression by suppressing the levels of miR-16, miR-143 and miR-203 in MCF-7 cells (35), consistent with the current findings.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings are consistent with previous studies [18] reporting increased expression of cell survival genes (AKT1, BCL2, XIAP, and BCL-XL) during increased proliferation. Consistent with the observation that insulin is a potent inducer of cell proliferation during development [19], we detected an upregulation of phosphorylated AKT and of proteins in the insulin/IGF-1 signaling pathway, including PI3K, IRS1, and S6K, in fibroblasts grown in defined Ax medium.…”
Section: Cells) (E)supporting
confidence: 93%
“…It has been suggested that the repression of miRNA by E2 is involved in the increased proliferation of mammary cells when stimulated with the hormone (Maillot et al, 2009;Yu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%